Building RAFT: Trafficking Screening Tool Derivation and Validation Methods. (23rd December 2019) - Chisolm‐Straker, Makini; Singer, Elizabeth; Rothman, Emily F.; Clesca, Cindy; Strong, David; Loo, George T.; Sze, Jeremy J.; d'Etienne, James P.; Alanis, Naomi; Richardson, Lynne D.
Abstract: Background: Labor and sex trafficking have long impacted the patients who seek care in emergency departments (ED) across the United States. Increasing social and legislative pressures have led to multiple calls for screening for trafficking in the clinical care setting, but adoption of unvalidated screening tools for trafficking recognition is unwise for individual patient care and population‐level data. Development of a valid screening tool for a social malady that is largely "invisible" to most clinicians requires significant investments. Valid screening tool development is largely a poorly understood process in the antitrafficking field and among clinicians who would use the tools. Methods: The authors describe the study design and procedures for reliable data collection and analysis in the development of RAFT (Rapid Appraisal for Trafficking). In a five‐ED, randomized, prospective study, RAFT will be derived and validated as a labor and sex trafficking screening tool for use among adult ED patients. Using a novel method of ED patient‐participant randomization, intensively trained data collectors use qualitative data to assess subjects for a lifetime experience of human trafficking. Conclusion: Study methodology transparency encourages investigative rigor and integrity and will allow other sites to reproduce and externally validate this study's findings.